09 F9 11 02 9D 74 E3 5B D8 41 56 C5 63 56 88 C0: Four Reasons Why AICP Needs an Open Data Ethic. Issue 2 (3rd April 2017) - Schweitzer, Lisa A.; Afzalan, Nader
Abstract : Problem, research strategy, and findings : Computing and digital technologies have changed how data are created, analyzed, and communicated. The American Institute of Certified Planners (AICP) Code of Ethics has no guidelines for planners working with emerging urban informatics. Here we make a theoretical argument based on the premise of epistemic justice: The idea that how planners collect, manage, disseminate, and use data all bear on justice in democratic decision making about cities. Four reasons exist for planners to prioritize open data in our formal code of ethics. First, emerging Big Data from urban informatics have a steep learning curve that potentially exacerbates the gaps in power and political voice between experts and nonexperts. Second, algorithms have come to govern an increasing portion of human life and cities, and planners should ideally be enabling residents in their ability to scrutinize, understand, and challenge managerial algorithms that have become prevalent in e-government. Third, urban informatics potentially alter the economic and community development of cities and the urban experience. Fourth and finally, ubiquitous data sensing, new consumer tracking capabilities, obscure and readily skipped terms of use agreements, and rapidly changing technologies make cities into potentially coercive data collection environments. Takeaway for practice : Substantial barriers exist to open data ethics in an information economy where exclusive access to data can drive profits. Emerging data systems can consolidate power in the hands of experts and large private firms to the exclusion of citizens and small, independent firms. Open data and code vitiates those problems to a limited degree, and AICP could benefit practitioners by adopting an open data ethic.